Inheritance right among the heirs of different religion: current legal analysis at Klang, Selangor / Mohammad Haizullmi Ismail - Ismail, Mohammad Haizullmi (2019)
Distribution of estate through inheritance process is an obligatory for the Muslim society to settle up as it has stated in Holy Quran and the manners are in the form of command. The purpose for the inheritances process is to provide the justice for the inheritor to survive in the future instead of protect their right in the distribution process. However, the existence of the heirs of different religion among the family member whose converts from other religion into others religion causes the arising of critical issue towards the distribution of the inheritance process. Regarding to this issues, there are some cases previously occur towards the distribution of the estate between Muslim and non-Muslim heirs in which the settlement must be done through the court law. Hence, the mains objective for this research paper is to identify the current legal analysis at Klang, Selangor pertaining to the distribution of estate among the heirs of different religion and also to find a new method of problem solving regarding to this issue. This research paper is using the qualitative method in which the data are collected through the case studies and by interview. The previous case study has revealed the impact that could be faced by the heirs and several factors that lead to the legal conflict in determining the variability of the heirs of different religion towards their right in inheritance distribution.